2011
DOI: 10.1111/j.1741-2358.2011.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a topical gel with triester glycerol oxide in denture‐related mucosal injuries

Abstract: The efficacy of a topical gel with triester glycerol oxide in denture-related mucosal injuriesObjective: The efficacy of a topical gel with triester glycerol oxide for treating ulcerations related to new complete dentures was studied and compared with a placebo gel. Materials and methods: Fifty edentulous patients were enrolled in this double-blind clinical study. All subjects received new maxillary and mandibular complete dentures and were recalled 1, 3 and 7 days after denture placement. Twenty-five subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Similar to our results, a 1996 study reported that patients claimed reduced healing time of aphthous ulcers due to treatment with bioadhesive hydrogel patches made from a pharmaceutical grade cellulose derivative . In contrast, application of topical gel with and without triester glycerol oxide (without containment in a patch) in denture‐related mucosal injuries was not effective for treating injuries from new full dentures . No prior reports have described the use of any hydrogel patch for denture‐related ulcerations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to our results, a 1996 study reported that patients claimed reduced healing time of aphthous ulcers due to treatment with bioadhesive hydrogel patches made from a pharmaceutical grade cellulose derivative . In contrast, application of topical gel with and without triester glycerol oxide (without containment in a patch) in denture‐related mucosal injuries was not effective for treating injuries from new full dentures . No prior reports have described the use of any hydrogel patch for denture‐related ulcerations.…”
Section: Discussionsupporting
confidence: 79%
“…14 In contrast, application of topical gel with and without triester glycerol oxide (without containment in a patch) in denture-related mucosal injuries was not effective for treating injuries from new full dentures. 15 No prior reports have described the use of any hydrogel patch for denture-related ulcerations.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge this is the first randomized, double-blind, placebo-controlled clinical trial investigating the effects of TGO gel in the treatment of RAS. In a placebo controlled study, the efficacy of TGO gel in the treatment of the ulcerations related to new complete denture have been investigated and TGO gel found ineffective (13). …”
Section: Discussionmentioning
confidence: 99%
“…Following its use a significant reduction of the number of erythrocytes and inflammatory cells and a significant increase of mature epithelial cells of oral mucosa were reported (13). TGO gel also has been shown to reduce RAS related symptoms, such as pain and was found effective in lengthening the duration of recurrence time (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation